Diet Quality in Midadulthood Predicts Visceral Adiposity and Liver Fatness in Older Ages: The Multiethnic Cohort Study. Issue 8 (August 2017) - Maskarinec, Gertraud; Lim, Unhee; Jacobs, Simone; Monroe, Kristine R.; Ernst, Thomas; Buchthal, Steven D.; Shepherd, John A.; Wilkens, Lynne R.; Le Marchand, Loïc; Boushey, Carol J.
Abstract : Objective: The relationship of diet quality assessed by established indices (HEI‐2010, AHEI‐2010, aMED, DASH) with adiposity measures was examined, especially visceral adipose tissue (VAT) and nonalcoholic fatty liver (NAFL). Methods: Close to 2, 000 participants of the Multiethnic Cohort completed validated food frequency questionnaires at cohort entry (1993‐1996) and clinic visit (2013‐2016) when they underwent whole‐body dual‐energy x‐ray absorptiometry and abdominal magnetic resonance imaging scans. Linear regression was used to estimate mean values of adiposity measures by dietary index tertiles at baseline and standardized regression coefficients (βs ) after adjusting for total adiposity and other covariates. Logistic regression of VAT and NAFL on dietary indices was also performed. Results: Higher dietary quality scores at cohort entry were inversely related to all adiposity measures, with the strongest associations for percent liver fat (βs = −0.14 to −0.08), followed by VAT (βs = −0.11 to −0.05), BMI (βs = −0.11 to −0.06), and total body fat (βs = −0.09 to −0.05). Odds ratios adjusted for total adiposity ranged between 0.57 and 0.77 for NAFL and between 0.41 and 0.65 for high VAT when comparing the highest versus lowest tertiles of diet quality. Conclusions: These longitudinal findings indicate that maintaining a high‐quality diet during mid‐to‐late adulthood may prevent adverse metabolic consequences related to VAT and NAFL.